Managing Online Learning to Support Inclusion During COVID-19 in A Private School in Dubai - AL-NAWAISEH, LANA JAMIL (2021)
The study aims to manage the pros and cons of online learning to support inclusion during the COVID-19 crisis at a private school in Dubai in the United Arab Emirates (UAE). Qualitative method was chosen by conducting semi-structured interviews. Data was collected from teachers, Special educational needs, and disabilities students (SEND) and the inclusion coordinator. Overall, students with special educational needs and impairments had mixed opinions towards online education, including both positive and negative aspects. The reason for this is that online learning is always a controversial topic. However, In COVID-19, students could not choose between online and traditional teaching because the UAE's ministry of education mandated that all students study distantly. Student disability type, willingness to change and academic institutions’ supports all play important roles in the long-term success of online learning. The findings show that online learning had some benefits and drawbacks for SEND students during the Covid-19 pandemic, which must be managed effectively to support the inclusion department in UAE schools. It indicates that most participants agreed that online education is safe during the crisis such as covid-19, saves time and provides an opportunity to learn new technical skills. However, the main disadvantage of online learning was that some students feel isolated in online learning because of the lack of face-to-face interaction between teachers and students and teachers can't monitor students' progress. As a result, they were unable to learn effectively since they were unable to communicate effectively with each other. The main recommendations of the study that students and teachers should be trained on new teaching principles and technologies to be ready for the future whether a crisis occurs or not. Moreover, policymakers should address the challenges of online learning from a new viewpoint to find a solution that accommodates all students and their needs. Consequently, the online learning experience that took place during the epidemic would be viewed differently by SEND students in various private and public schools. Therefore, it is recommended that the study include a larger sample of SEND pupils from all UAE schools to increase the validity of the findings. A further limitation of the study was the limited number of previous studies. This is in addition to depending solely on interviews due to the UAE's social distance rules.